ANAK SEBAGAI PEDAGANG MAKANAN KELILING DI DENPASAR BARAT : ANALISIS KETEGANGAN STRUKTUR SOSIAL - Eka Suartika, Ida Ayu; Zuryani, Nazrina; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI (SOROT), 2014)
ABSTRACT Child (12-16 years old) as food peddler in the area of West Denpasar classified as child labour because they work beyond what ILO Convention No. 138 allowed for. According to UU No. 1 in 2000, they do a dangerous job like selling and bringing foods around the streets in Denpasar. This study conducted during November 2013 until July 2014 within depth interview, observation, and study document. Data analyses showed that the reason why they became child food peddler because three factors such as economic, natural environment, social culture environment and education factor. Merton’s strain social structure analyzed that organized behavior and the appearance of child peddler due to limited access which given by social structure where they came from, create strain condition. The social culture impact is they reluctance to continue their education, they using harsh language, early sex activity, and they less attention about their health being. Keywords : Child, Food Peddler, Strain Social Structure